The Effects of Transformational Behaviours and Interpersonal Skills of Leadership on Organisational Citizenship Behaviour: Trust in the Leader as a Mediator in Libyan Commercial Banks - Salim Mohamed Salem (Universiti Sains Islam Malaysia, 2024)
The employees’ behaviour, especially organisational citizenship behaviour (OCB) has received widespread interest in organisational literature in various institutions. Based on critical reviews by the researcher of references and sources, the importance of trust in leader and the leaders’ behaviours in encouraging employees to engage in OCB has become evident. According to Social Exchange Theory, transformational leadership behaviours (TLB) affect OCB often through a mediator such as trust in the leader. Empirical research has shown that TLB can directly or indirectly through trust in leader affect OCB. Accordingly, the present study combined these elements into one theoretical framework with a new contribution represented in the leader’s interpersonal skills. In this regard, the banking sector in Libya suffers from several problems, the most important of which is the focus on official relations and the omission of social relations, which in turn causes the low level of organisational citizenship behaviour directed to employees (OCBI) among employees. In addition, interviews with some employees in commercial banks revealed that the symptoms of low OCBI among employees were unsatisfactory and uninspiring work environment as well as the prevalence of prevalence of counterproductive work behaviours such as anger, aggression and absenteeism. This research focused on the impact of TLB and interpersonal skills of leadership on OCBI in commercial banks in Libya,as well as the role of trust in the leader as a mediator in the relationship. To achieve these objectives,a questionnaire was developed that confirmed its reliability and validity and distributed to 450 proportional stratified samples of employees from four commercial banks in Libya. The number of valid questionnaires was 337. SPSS version 22 was used to describe the study population, conducting exploratory factor analysis and reliability, while Amos used the 22 version to test the hypotheses. The findings of the study indicated that the TLB directly affects both trust in the leader and the OCBI and indirectly through trush, while interpersonal skills of leadership did not directly affect the OCBI except through trust in the leader.On the other land, not all transformational behaviours and interpersonal skills have direct effects on altruistic and ciurtesy behaviours. In addition, there is no any pattern of trust in leader mediates the relationship between components of both behaviours, interpersonal skills of leadership and dimensions of OCBI were mediated. Based on the results of the study, some recommendations were proposed to improve the OCBI among employees in commercial banks, including: developing the dynamics of relations between managers and employees, exceed self- interests to build trust on a solid basis, and promoting the concept of altruistic and courtesy behaviours among employees to reduce some undesirable behaviours such as counterproductive work behaviours, absenteeism, and turnover.